Cardiovascular mortality during heat and cold events: determinants of regional vulnerability in Taiwan. Issue 7 (29th October 2010) - Wu, Pei-Chih; Lin, Chuan-Yao; Lung, Shih-Chun; Guo, How-Ran; Chou, Chang-Hung; Su, Huey-Jen
Abstract : Objectives: To identify the vulnerable regions with underlying susceptibility and poor adaptive capability in response to cold and heat events in Taiwan, and to characterise the determinants associated with such an increasing risk to design better adaptive strategies in view of predicted weather changes in the future. Methods: The authors used spatial regression models to measure the relationships between the spatial characteristics of temperature, extracted factors from demographic and socio-economic parameters, and the mean cardiovascular mortality 2 weeks before and after cold or heat events from 1994 to 2003. Results: Metropolitan regions were found to have a substantially lower mortality than rural areas after cold and heat events. Events of cold, compared with heat, had greater impacts on the mortality ratio in most townships. A negative association was identified, using a spatial lag model, between the mortality after cold and heat events and urbanisation, and the availability of medical resources. A higher percentage of older people, vulnerable and aborigines might have contributed to the increasing vulnerability of townships during cold and heat events. Conclusions: These data, using an island-wide spatial analysis, suggest that urban areas have a greater adaptive capability than rural areas, plausibly because people in urban areas have a higher socio-economic status and more medical resources. Social inequality across urban and rural townships is apparent and developing customised adaptation programmes for vulnerable regions to cope with heat and cold event should be prioritised.